2012
DOI: 10.1371/journal.pone.0046483
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Promotes Osteogenesis but Suppresses Adipogenesis of Human Mesenchymal Stromal Cells in a Hypoxia-Inducible Factor-1 Dependent Manner

Abstract: BackgroundBone fracture initiates a series of cellular and molecular events including the expression of hypoxia-inducible factor (HIF)-1. HIF-1 is known to facilitate recruitment and differentiation of multipotent human mesenchymal stromal cells (hMSC). Therefore, we analyzed the impact of hypoxia and HIF-1 on the competitive differentiation potential of hMSCs towards adipogenic and osteogenic lineages.Methodology/Principal FindingsBone marrow derived primary hMSCs cultured for 2 weeks either under normoxic (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 34 publications
13
120
1
Order By: Relevance
“…Previous studies have indicated that MSCs can be recruited by osteocytes under hypoxia, and genetic activation of the HIF-1α pathway increases neoangiogenesis and promotes bone regeneration (13). The present study identified that CoCl 2 was able to significantly increase the expression of Runx2, ALP and OC.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have indicated that MSCs can be recruited by osteocytes under hypoxia, and genetic activation of the HIF-1α pathway increases neoangiogenesis and promotes bone regeneration (13). The present study identified that CoCl 2 was able to significantly increase the expression of Runx2, ALP and OC.…”
Section: Discussionsupporting
confidence: 60%
“…(109)]. Moreover, osteoblast differentiation at the expense of adipocyte differentiation was shown to be HIF-1a mediated in human stromal precursors (110). Taken together, we suggest the following: In the BM, immature stromal cells are able to retain their undifferentiated state and maintain their role in supporting primitive hematopoietic cells due to low ROS levels (also in the hematopoietic cells).…”
Section: Ros Mediates Proliferation and Differentiation Of Bm Mesenchmentioning
confidence: 73%
“…Note that VEGF, GLUT1, LDHA, PGK1 genes are target genes of HIF-1a. 81 Previous data showed an increase in PDK1 gene expression. These data confirm that reduced cell respiration under hypoxic conditions is an outcome of the reduction of mitochondrial oxygen consumption.…”
Section: 83mentioning
confidence: 97%